Dynamical Analysis of Non-Fourier Heat Conduction and Its Application in Nanosystems - Dong, Yuan (Springer Theses, Recognizing Outstanding Ph.D. Research, 2016)
This thesis studies the general heat conduction law, irreversible thermodynamics and the size effect of thermal conductivity exhibited in nanosystems from the perspective of recently developed thermomass theory. The derivation bridges the microscopic phonon Boltzmann equation and macroscopic continuum mechanics. Key concepts such as entropy production, temperature and the Onsager reciprocal relation are revisited in the case of non-Fourier heat conduction. Lastly, useful expressions are extracted from the picture of phonon gas dynamics and are used to successfully predict effective thermal conductivity in nanosystems.